Coping patterns of high-and low-anxious soldiers a psychosocial study.[article]. - Dayan, Natividad A.
Seventy-two soldiers from the Philippine Marines, classified into high-and low-anxiety groups, served as subjects for this study. Data analysis included determination of differences in the demographic and personality variables, and testing the hypotheses that the two groups differed in the types of coping mechanisms used; on the effectiveness of their coping strategies, and on efficiency on the job. Very slight differences were noted relative to the demographic and personality correlates, but exceptions were seen in the tendency of the high-anxious group to cite family discord as a major problem that faced their families; and in the presence of more non-commissioned ranks in the low-anxious group was found less likely to resort to active-aggressive, passive-hostile and escape coping mechanisms, although there was similarity in the use of the acceptance coping strategy. The two groups differed significantly in the appropriateness of response to the situations involving family crisis and personal threat. The hypothesis that the low-anxious soldiers are rated as more efficient than high-anxious soldiers was supported.